Environment and economic burden of sustainable cooling/lubrication methods in machining of Inconel-800. (10th March 2021) - Gupta, Munish Kumar; Song, Qinghua; Liu, Zhanqiang; Sarikaya, Murat; Jamil, Muhammad; Mia, Mozammel; Singla, Anil Kumar; Khan, Aqib Mashood; Khanna, Navneet; Pimenov, Danil Yu
Abstract: The present work deals with the machining application of one of the aerospace material i.e., Inconel-800 alloy by considering the social, economic and environmental effects. The turning tests were done under four sustainable machining conditions i.e., dry, vegetable oil with minimum quantity lubrication (MQL) system, graphene nanofluid plus vegetable oil with MQL (NMQL) system and liquid nitrogen (N2 ) cooling. Then, the energy consumption, carbon emissions, cost per part, average surface roughness and cutting tool wear have been measured for varied cutting speed and feed rate under selected sustainable environments. The outcomes of this study revealed that the N2 cooling conditions reduced the total machining cost up to 9.3%, total energy consumption up to11.3%, carbon emissions up to 49.17% and tool wear up to 46.6% as compared to other cooling conditions. Significant improvement in surface roughness and tool wear have also been noticed from the outcomes of N2 cooling conditions. Hence, it is worthy to mention that these cooling conditions promote sustainability in the aerospace sector by saving resources and extending environmental benefits. Graphical abstract: Image 1 Highlights: Turning of Inconel-800 alloy under dry, MQL, NMQL and liquid N2 conditions were performed. Sustainability in terms of machining efficiency, carbon emissions, energy consumption and cost modelling were evaluated. Overall sustainability aspects were improved with liquid nitrogen cooling. Machinability indicators such as surface roughness and tool wear were also improved with liquid nitrogen cooling.